Examining the Differences in Biomarkers of Neuronal and Glial Injury Between Autoimmune Neurologic Disease Patients and Healthy Controls. (5th December 2022) - Borko, Tyler L.; Barrera, Britney; Mizenko, Christopher; Ledreux, Aurélie; Kammeyer, Ryan; Ritchie, Alanna; Selva, Sean; Sillau, Stefan; Engebretson, Eric; Seale, Rebecca; Valdez, Brooke; Bennett, Jeffrey L.; et al.
Abstract : Objective: To evaluate differences in concentrations of serum-based biomarkers obtained from a screened healthy control (HC) population compared to age and sex matched autoimmune and inflammatory neurologic disease (AIND) patients. Background: Protein markers of neuronal and glial injury have become important, minimally invasive biomarkers for understanding the impact of disease in various neurological disorders, including ongoing research into AINDs. Levels of these proteins in healthy individuals remain unclear. Design/Methods: Neurofilament light (NfL), glial fibrillary acidic protein (GFAP), ubiquitin carboxyl-terminal hydrolase L1 (UCH-L1), and total tau (Tau) levels in AIND and HC participants will be compared. Multiple Sclerosis (MS) patients, as inflammatory controls, will be analyzed as well. AIND and HC participant serum samples have been collected to obtain NfL, GFAP, UCH-L1, and Tau protein levels using Quanterix SR-XTM SIMOA. We plan to analyze and compare age and sex matched HC samples to AIND patients for each biomarker, ages ranging from 20-80 years old. Concentrations will be log transformed and analyzed with mixed model regression. Results: Healthy Controls (130), AIND (255), and newly diagnosed/treatment naïve MS samples (681) have already been collected. Nineteen HC and AIND (includes NMDA, LGI1, TRIM46, CRMP5, MOG, DPPX, GABA-A, GAD-65) participants were analyzed. Preliminary results for HC show mean Nfl (10.3 pg/mL), GFAP (78.9 pg/mL), UCH-L1 (5.65 pg/mL), and Tau (0.53 pg/mL) levels, and for AIND patients mean Nfl (186.48 pg/mL), GFAP (434.92 pg/mL), UCH-L1 (71.38 pg/mL), and Tau (51.85 pg/mL) levels. While ongoing biomarker analysis will be completed with HC that are age and sex matched, the significantly higher levels in AIND patients highlights the importance of creating baseline values in HC to understand these same biomarkers in AIND patients. Conclusions: Preliminary results show NfL and GFAP levels are significantly higher in AIND patients versus HC. Baseline biomarker values are essential for understanding further research in biomarkers related to AIND.